Mechanical behavior of snake grass fiber with neem gum filler hybrid composite - Arumugam Pachiappan; Senthil Kumar Velukkudi Santhanam (Polímeros, 2023)
Abstract In this study, the utilization of neem gum powder and snake grass fiber, gathered from snake grass plants is discussed. The fibers are produced in various volume percentages of 5, 10, 15, 20, 25, 30 and 35% and their mechanical characteristics such as tensile strength, flexural strength, impact strength, and critical stress intensity are investigated. The combination of 30% snake grass fiber, 15% neem gum powder and 55% epoxy resin, in terms of volume, contributes towards the attaining of better mechanical properties. The tensile strength, flexural strength, impact strength, and critical stress intensity of this blend are respectively 36.497±0.429 MPa, 65.87±1.85 MPa, 2682.67±1.866 J/m2 and 42.291±2.61 Pa mm-1/2. The mechanical properties improve with the addition of the fiber. However, as more fiber is added, the adhesion at the interface gets reduced. The automotive and aerospace sectors can use this composite material, which enhances the mechanical characteristics for interior applications.